2015
DOI: 10.1083/jcb.201411003
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for assembly and function of the Nup82 complex in the nuclear pore scaffold

Abstract: The yeast Nup82 complex forms an unusual asymmetric structure with a dimeric array of subunits that mediate its anchorage to the NPC scaffold and its concomitant interaction with the soluble nucleocytoplasmic transport machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 78 publications
13
93
0
Order By: Relevance
“…2). Nup82, Nup159, together with a pool of Nsp1 that is separate from the central Nsp1-Nup57-Nup49 complex, form a trimeric 1:1:1 complex at the base of the filaments [48,83]. The three proteins are likely held together by an interaction between their C-terminal coiled-coil regions.…”
Section: Components Of the Cytoplasmic Sidementioning
confidence: 99%
“…2). Nup82, Nup159, together with a pool of Nsp1 that is separate from the central Nsp1-Nup57-Nup49 complex, form a trimeric 1:1:1 complex at the base of the filaments [48,83]. The three proteins are likely held together by an interaction between their C-terminal coiled-coil regions.…”
Section: Components Of the Cytoplasmic Sidementioning
confidence: 99%
“…Recent structural data for a reconstituted Nup82 module suggest that the C-terminal portion of Nup159, which includes the DID and the C-terminal helices, forms the structural backbone of the complex, along which the other subunits – Nup82, Nsp1, and Dyn2 – become organized, and that this segment of Nup159 is required for organization of the whole complex [105]. Critical to this process is a short, weakly predicted coiled-coil sequence separated from the DID domain by a flexible linker, and shown in vivo to be essential for NPC assembly [98].…”
Section: Lc8 Cross-linking Of Idp Duplex Scaffoldsmentioning
confidence: 99%
“…The core of the Nup82 complex is composed of the proteins Nup82, Nup159, and Nsp1. Fragments of each have been solved crystallographically (Chug et al, 2015; Stuwe et al, 2015a; Yoshida et al, 2011), and negative stain EM revealed this complex to have an overall “P-shaped” morphology (Gaik et al, 2015), but no structures exist for either the whole complex or how it interacts with its associated proteins and the NPC.…”
Section: Introductionmentioning
confidence: 99%